(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Unhealthy diets and lifestyles cause a resistance to and/or relative deficiency of insulin production. Therefore, it is thought worthwhile to develop a natural remedy that may effectively manage the disease symptoms to a certain extent without causing adverse consequences. The objective was to develop the active biological constituent(s) for the use of Coccinia indica and its relationship to treating type II diabetic rats. The soxhlet extraction method was used to get the cocktail of phytochemicals of C. indica by using methanol. The composition of a high-sugar diet, followed by fructose (66%), was used to induce T2DM in rats. The preliminary predictive markers were body weight (pre- and post-treatment), blood glucose level (pre- and post-treatment), serum insulin, and pancreatic insulin. And the secondary outcomes were the pro-inflammatory mediators interleukin 6 (IL-6), transforming growth factor-β (TGF-β), and tumour necrosis factor alpha (TNF alpha). Additionally, pancreatic tissue was used to estimate beta cell mass, size, and necrosis, and the cell supernatant was used to observe superoxide dismutase (SOD), lipid peroxidation (LPO), and catalase (CAT). High sugar diet showed significant increase in body weight (p < 0.01), fasting blood glucose level (p < 0.001), and decrease in serum and pancreatic insulin levels (p < 0.001), whereas rats treated with methanolic extract of C. indica showed significant reduction in post-treatment body weight (p < 0.01), blood glucose levels (p < 0.01), and increase in serum and pancreatic insulin (p < 0.001), especially in higher doses, i.e., 400 mg/kg. Pro-inflammatory cytokines (IL-6, TGF-beta, and TNF-α) can increase insulin resistance, which results in poor glucose homeostasis, which has been reduced by treatment with C. indica (p<0.001). Superoxide radicals and a deficiency in catalase, both of which are linked to diabetes, but the extract of the plant has been shown to enhance the secretion of enzymes SOD and CAT (p<0.001). It has been proven to have a crucial role in the regulation of apoptosis because it lowers oxidative stress and similarly reduces the level of LPO (p<0.01). Additionally, the treated rat pancreas shows islets of Langerhans that are normal in number and size. No necrosis or reduction in size was seen. The current study conclusively shows that the phytoconstituents of C. indica have the potential to tackle long-term health complications and manage symptoms.